A HEALTHY BUSINESS COMPETITIONING PARTNERSHIP - Aprasing, Andi (Journal of Humanity, 2013)
To achieve the development goals the Government continually carry out national development based on the practice of Pancasila which covers all aspects of the life of the nation. Government as the highest power organization authorized to redirect and protect the public in the exercise of its activities through the partnership, sometimes business medium/large businesses treat small businesses not as it should be. That means big business did not help the development of small businesses and even the large business partnership is increasingly growing, the partnership merely proves that big companies care about the social environment and small businesses less benefit as purpose partnerships that help the development of small businesses.